STUDENT’S ACQUISITION OF INFERENTIAL THINKING IN MATHEMATICS AND ITS TRANSFER TO OTHER SUBJECT AREAS - France, Ilze; Krieviņa, Liene (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Due to education reform in Latvia, the tendency in education is competence approach with transversal skills as one of its elements. They are included in the state education standard which all the teachers shall carry out in the corresponding education period. All educational establishments face a real challenge of how to implement the planned competences in life. The present research focuses on one of the skills of critical thinking – inferential thinking. By the help of inference students compare information obtained and the results to either confirm or decline their hypothesis, considering the accuracy of the acquisition of the information. The goal of the research is to make and test a system how an educational establishment should organize the study process to teach and develop inferential thinking. The following methods were used in the research: partly structured interviews with the vice-principal in methodological work and teachers of subjects, analysis of methodological materials and analysis of students` written works. The research was carried out to find what the most essential preconditions for students to learn and develop inferential thinking skills are and how to make transfer to various fields to improve learning those skills. A conclusion was made that a purposeful and organized cooperation of teachers plays an important role in teaching transversal skills. The results are better if students can reflect on their achievements using unified description of performance level in all subjects thus implementing the transfer of skills in other subject areas. To teach a skill teacher must plan specific steps to teach and to develop the skill. A model to develop the skill `inferential thinking` has been worked out and tested in the subject of mathematics and is meant to be improved in other subject areas in grade 7.